Analysis of the Cutting Parameters Influence During Machining Aluminium Alloy A2024-T351 with Uncoated Carbide Inserts - HADDAG, Badis; ATLATI, Samir; NOUARI, Mohammed; BARLIER, Claude; ZENASNI, Mohammed (Engineering Transactions, 2012)
This work aims to analyze the effect of the cutting parameters on chip segmentation of the aluminium alloy A2024-T351 during machining process. In this work, two parameters are considered: the tool rake angle of the cutting tool and the feed under dry machining. An orthogonal cutting FE model is developed in Abaqus/Explicit for this purpose. A thermo-visco- plastic-damage model for the machined material and thermo-rigid behaviour for the cutting tool have been assumed. At the chip/tool contact zone, the modified Coulomb friction model has been adopted. Thermal effects are considered by taking into account the heat flux generated by visco-plastic strain and also by friction at the tool-workpiece interface. The obtained results showed the effect of the tool rake angle and feed on the cutting force and chip morphology as well as temperature distribution at the tool rake face.